Analyzing organizational ideology: A workplace assessment exercise - King, Albert S. (International journal of value-based management, 1996)
This paper provides an experiential exercise to increase understanding of employees’ attraction to ideological organizations and its relation to employees’ perception of loyalty, value congruence, and affective organizational commitment. Three separate conditions influencing employee attraction to organizational ideology are loyalty, value congruence, and affective commitment. These three component dimensions of employee attraction are outlined and used to define an eight-phase model through which individuals tend to pass in their decision to form and join ideological organizations., The analysis supports the notion of a stepwise movement from loyalty to value congruence to perceived commitment in strengthening ideological attraction and demonstrates how progressive phases are associated with perceived quality and connection to ideological organizations. Although the levels and phases are progressively prepotent and attractive in predicting employee propensity to form and join ideological organizations, different patterns and paths through the phases for individuals are indicated., The workplace assessment exercise is a tool that will permit managers and professionals to make first order assessments of quality of work life. This survey will discover which personnel and/or jobs are most strongly bonded to the organization and which are the most likely candidates for intervention and revitalization.